The crystal structure of 2-(2-(2,3,4,9-tetrahydro-1H-pyrido[3,4-b]indol-2-ium-1-yl)phenoxy)acetate, C19H18N2O3 - Li-Hua Wang; Xi-Shi Tai (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C19H18N2O3, monoclinic, P21/c (no. 14), a = 12.6187(7) Å, b = 9.4445(5) Å, c = 13.7424(8) Å, β = 99.248(5)°, V = 1616.49(16) Å3, Z = 4, Rgt(F) = 0.0793, wRref(F2) = 0.2220, T = 100(10) K.